Keefektifan Discovery Learning Melibatkan Kearifan Lokal Pada Pembelajaran Matematika Siswa Kelas VIII SMPN 1 Tompobulu - Nurdin R.; Baharuddin; Khadijah (GENIUS: Jurnal Inovasi Pendidikan dan Pembelajaran, 2024)
This study is pre-experimental quantitative research involving one group, namely the experimental group. The population of the study were all grade VIII students at SMPN 1 Tompobulu in Gowa district, which consisted of 3 classes and the sample was determined by using cluster random sampling technique. The instruments of the study were (1) learning outcomes test, (2) student‟s activity observation sheets, and (3) student‟s response questionnaire. The data analysis technique used were descriptive analysis and inferential analysis. The indicators of learning effectiveness in this study are (1) learning outcomes, (2) students‟ activities, (3) students‟ responses. If the three indicators meet the standards set, then the learning is categorized as effective. Based on descriptive and inferential statistical analysis using the t-test, it is discovered that (1) the learning outcomes achieved classical completeness, which is 87% above the ideal completeness; (2) the students‟ activities are in very good category, namely 3.5; (3) the students‟ responses are in good category, namely 3.27. Based on the results of inferential statistical analysis, it is obtained a significant value of p = 0.000 < α = 0.05, this means that H0 is rejected and H1 is accepted, namely the use of discovery learning model involving local wisdom in Pythagorean Theorem material is effective. Therefore, the discovery learning model involving local wisdom is effectively applied to grade VIII students at SMPN 1 Tompobulu in Gowa Distirict.